Attitudes Towards the Southern and Northern Samogitian Subdialects of the Young Generation: Gender Based Comparative Study - Zablockytė, Rimutė; Kačiuškienė, Genovaitė (Jaunųjų mokslininkų darbai, 2017)
The aim of the paper is to find whether and when the Samogitian dialect is used, whether it is worth using a native dialect and attitudes towards a dialect and standard Lithuanian. A quantitative survey method was used to identify attitudes towards Southern and Northern Samogitian and their use. Research sample: 100 respondents with non-humanitarian education from Northern and Southern Samogitia, aged 18-30. The survey showed that the majority of the respondents only sometimes used their dialect, usually with interlocutors from the same village or town. The respondents were well aware of the domains where a dialect can be used, knew that it should be used in informal speech, informal situations and used standard Lithuanian in formal speech. It was found that it was important to them to preserve the Southern and Northern Samogotian subdialects. Having compared the respondents‘ answers by gender no significant difference was found between the opinion of men and women about the use and preservation of their native dialect.